In vitro plant regeneration through protocorm formation in orchid Calanthe odora - GANTAIT, SUBHENDU S; DATTA, KOUSHIK; THOKCHOM, ROCKY (The Indian Journal of Agricultural Sciences, 2020)
The regeneration of plants through formation of protocorm and protocorm-like bodies was achieved by in vitro asymbiotic immature seed culture of Calanthe odora. This is the first report on in vitro regeneration of plantlets of Calanthe odora Griff., the IUCN red listed threatened species. The immature seeds as explants were most regenerative than mature seeds. The MS media fortified with different concentrations of Kinetin alone or in combination with NAA were tested to sort out as the best regeneration media. From the experimental results the best medium was sorted as MS medium supplemented with 1.0 mg/l Kinetin and 1.0 mg/l NAA for germination and formation of protocorm-like bodies from immature seed explants followed by transfer to MS media fortified with 1.5 mg/l Kinetin and 1.0 mg/l NAA for development of protocorm to plantlets. The plantlets after hardening in in vitro were transferred to polyhouse where 86.7% survival rate was recorded on vermiculite potting media.